WHY I BUY ORGANIC PRODUCTS – PERCEPTION OF MIDDLE INCOME COUNTRY CONSUMERS (REPUBLIC OF SERBIA) - Milić, Dragan; Tomaš Simin, Mirela; Glavaš - Trbić, Danica; Radojević, Vuk; Vukelić, Nataša (Economics of Agriculture, 2022)
The research was conducted on consumers and potential consumers of organic products in Serbia. In countries with average low incomes, knowledge of the organic products market is important because one of the often singled out characteristics of organic products is their premium price. Knowing the motives of potential consumers of these products and the characteristics that they value more gives the opportunity to improve this production. The research involved 496 respondents, older than 18, with different levels of education, marital status and other socio-demographic characteristics. The results showed that a healthy, quality product, which has no additives and harmful substances and has the best price-quality ratio with a clearly defined shelf life, are the basic factors for buying food products, the factors that most influence a positive purchase decision. The authors conclude that highlighting these characteristics in organic products can lead to further development of this market.